Moral cognition and homicide amongst forensic patients with schizophrenia and schizoaffective disorder: A cross-sectional cohort study - Corvin, Aiden; Kennedy, Harry (My University, 2018)
Abstract Forensic patients with schizophrenia who had carried out a homicide scored higher on a measure of moral cognition (MFQ-30) than other violent patients. Neurocognitive impairment was associated with homicide by mediation via higher scores for in-group loyalty.
PUBLISHED